MicroRNAs as Immune Regulators: Implications for Transplantation - Harris, Aleishia (2010)
The explosion of genetic information from recent advances in sequencing technologies, bioinformatics and genomics, highlights the importance of understanding mechanisms involved in gene expression and regulation. Over the last decade it has become clear that small RNAs are a central component of the cellular gene regulatory network. MicroRNAs (miRNAs) are a family of endogenous, small, non-coding single-stranded RNA of ~22 nucleotides in length that act as post-transcriptional gene regulatory elements. MiRNAs can inhibit de novo protein synthesis by blocking translation through base-pairing with complementary mRNA and also suppress translation by promoting degradation of target messenger RNA (mRNA). MiRNAs are intimately involved in a variety of biologic processes including development, hematopoietic cell differentiation, apoptosis, and proliferation. To date over 800 human miRNAs have been identified, though the biologic function of only a fraction of miRNAs have been elucidated. Here we discuss how miRNAs are produced, identified, and quantitated, and focus on several key miRNA that govern expression of genes relevant to allograft rejection, tolerance induction, and post-transplant infection. Finally, we discuss potential ways in which the miRNA network can be modulated that ultimately may offer new strategies to promote long-term graft survival.